The development dynamics and spreading peculiarities of the pathological process in the retroperitonael space in acute pancreatitis - V. V. Ganzhy; I. P. Kolesnyk; N. A. Yareshko; A. I. Marusiy (Zaporozhye State Medical University, 2015)
Despite rapid development of medicine, acute pancreatitis (AP) is still a problem. Aim. To evaluate pathological changes of retroperitoneal space (RS), the results of ultrasound research, computed tomography and laparoscopy were studied in 62 patients with severe form of AP. Methods and results. Our own improved division of retroperitoneal space was used during work. It was based on already existing classification and it's simple and can be used in everyday practice. It was revealed that infiltrative changes of RS develop more often in patients with edematous form of disease. In patients with necrotic form infiltrative changes as well as liquid ones can develop in the RS. The more extensive is pancreas necrosis, the higher is the probability that greater number of anatomic areas will be involved into the pathological process. It was noticed that complications appear more often in patients with liquid changes in the RS as well as they have higher percentage of mortality. Conclusion. Thereby, dynamic observation of area and depth of pathological process spreading, its condition allows deciding on correct treatment strategy.